Intravenous tranexamic acid for hyperacute primary intracerebral hemorrhage: protocol for a randomized, placebo-controlled trial - Sprigg, Nikola; Robson, Katie; Bath, Philip M.W.; Dineen, Robert A.; Roberts, Ian; Robinson, Tom; Roffe, Christine; Werring, David; Al-Shahi Salman, Rustam; Pocock, Stuart J.; Duley, Lelia; England, Timothy J.; et al. (SAGE, 2016)
Rationale: Outcome after intracerebral hemorrhage remains poor. Tranexamic acid is easy to administer, readily available, inexpensive, and effective in other hemorrhagic conditions.